2000
DOI: 10.1177/000992280003900201
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Factors of Acute Aortic Dissection in Children and Younrg Adults

Abstract: Current concepts in the pathophysiology and predisposing conditions of acute aortic dissection in children, adolescents, and young adults are presented. Timely diagnosis is required for this life-threatening condition. Most children and adolescents with aortic dissection have congenital cardiovascular anomalies. Certain heritable disorders involving connective tissue also predispose to this disorder. Newer associations include cocaine abuse and weight lifting. To facilitate early diagnosis, the salient physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 44 publications
2
68
0
3
Order By: Relevance
“…15 Conditions that weaken the aortic medial layer predispose to aortic dissection. 11,15,16 Some reports have indicated that congenital cardiovascular anomalies are the most common predisposing conditions for acute aortic dissection occurring in the pediatric population. 5 Traumatic aortic dissections are usually stated to be very rare.…”
Section: Introductionmentioning
confidence: 99%
“…15 Conditions that weaken the aortic medial layer predispose to aortic dissection. 11,15,16 Some reports have indicated that congenital cardiovascular anomalies are the most common predisposing conditions for acute aortic dissection occurring in the pediatric population. 5 Traumatic aortic dissections are usually stated to be very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Aort diseksiyonu için risk faktörleri genel olarak hipertansiyon, arterioskleroz, Marfan sendromu ve Tip IV Ehlers Danlos sendromu gibi herediter bağ dokusu hastalıkları, fibromuskuler displazi, aortun intrensek anomalileri, aort kapak anomalileri, gebelik, aortun inflamatuar hastalıkları, ağır fiziksel egzersiz ve ağırlık kaldırma, travma, aorta yapılan cerrahi ve tıbbi girişimler ve kokain kullanımı olduğu bildirilmektedir (5). Bizim olgumuzda bilinen herhangi bir hastalığın olmadığı belirtilmiştir.…”
Section: Discussionunclassified
“…Ani göğüs ve/veya bel ağrısı ile karakterize olan aort diseksiyonu, yaşamı tehdit etmektedir (4). Etiyolojisinde hipertansiyon, ateroskleroz, Marfan ve Ehler Danlos gibi hastalıklar yer almaktadır (5,6). Amerika Birleşik Devletleri'nde insidansı yılda milyonda 5-30 olgu arasında değişmektedir (7).…”
Section: Introductionunclassified
“…Although progressive dilatation of the ascending aorta has been described in pediatric patients with bicuspid aortic valve (BAV), the occurrence of aortic dissection is rare (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%